2022
DOI: 10.1259/bjr.20220206
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming challenges of translating deep-learning models for glioblastoma: the ZGBM consortium

Abstract: Objective: To report imaging protocol and scheduling variance in routine care of glioblastoma patients in order to demonstrate challenges of integrating deep learning models in glioblastoma care pathways. Additionally, to understand the most common imaging studies and image contrasts to inform the development of potentially robust deep learning models. Methods: MR imaging data were analysed from a random sample of 5 patients from the prospective cohort across five participating sites of the ZGBM consortium. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 6 While not the focus of our study which incorporates all patients consecutively (including complete response, partial response, stable disease, progression, and pseudoprogression), interpreting post-radiotherapy structural MRIs in clinical settings is typically challenging due to difficulty in distinguishing recurrent disease from treatment-related effects—particularly for pseudoprogression. 2 , 3 , 6 , 11 , 17 , 36–38 However, labelling progression—and pseudoprogression—requires the availability of repeated T1c imaging obtained in a timely manner per patient, accompanied by accurate measurements of bidirectional diameters of contrast-enhancing tumors. 37 , 38 Prior research has reported that there can be substantial inter-rater variability in these measurements, however, which can confound evaluations of treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 While not the focus of our study which incorporates all patients consecutively (including complete response, partial response, stable disease, progression, and pseudoprogression), interpreting post-radiotherapy structural MRIs in clinical settings is typically challenging due to difficulty in distinguishing recurrent disease from treatment-related effects—particularly for pseudoprogression. 2 , 3 , 6 , 11 , 17 , 36–38 However, labelling progression—and pseudoprogression—requires the availability of repeated T1c imaging obtained in a timely manner per patient, accompanied by accurate measurements of bidirectional diameters of contrast-enhancing tumors. 37 , 38 Prior research has reported that there can be substantial inter-rater variability in these measurements, however, which can confound evaluations of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…These sequences were consistently acquired at all centers; conversely, more advanced MRIs are less commonly available. 17 , 18 Incorporating other anatomical sequences desirable for brain tumor imaging, such as FLAIR sequences, was not also pursued as it would have reduced the patient cohort in this UK-based study where FLAIR imaging was not always performed. A downstream constraint of building a model without the most common MRI sequences is that it reduces the potential for clinical translation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that deep learning AI sequences can reduce scanning time by 45% − 60% while keeping spatial resolution constant (2931). This improves patient experiences and scanner efficiency without sacrificing diagnostic quality, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%